Factors Influencing Pilgrimage Destinations: The Location of Calvaries and Stations of the Cross in Slovakia - Matlovic, René (Turyzm/Tourism, 2005)
The article deals with destintions for pilgrimage in Slovakia; it includes a basic typology of pilgrimage destinations with characteristics of their hierarchic and spatial structure.